Evaluation of Streptomyces sporoverrucosus B-1662 for biological control of red pepper anthracnose and apple bitter rot diseases in Korea - Kim, DaYoung; Kim, Jungyeon; Lee, Younmi; Balaraju, Kotnala; Hwang, Ye-Ji; Lee, Mi-Hwa; Cheon, Wonsu; Mun, Hye Yeon; Lee, Chang Soo; Jeon, Yongho (Frontiers in Microbiology, 2024)
Fungi are the prominent phytopathogens that have significant impact on the productivity of agriculture worldwide. Streptomyces species have been extensively studied for the production of various bioactive metabolites. These metabolites have been used as biocontrol agents for the management of diseases caused by phytopathogenic fungi. The purpose of this investigation is to assess the efficacy of Streptomyces sporoverrucosus B-1662, an antagonistic agent in the control of red pepper anthracnose caused by Colletotrichum acutatum KACC 42403 and apple anthracnose caused by Colletotrichum siamense CGCP6 (GYUN-10348). On the basis of the morphological, and molecular characterization using 16S rRNA, the strain B-1662 was determined to be S. sporoverrucosus. The strain B-1662 exhibited antagonistic activity against seven fungal phytopathogens, including C. acutatum KACC 42403 and C. siamense CGCP6. The culture filtrates (CF) from B-1662 showed antifungal activity against all seven fungal pathogens with greater inhibition rate (%) in comparison with a control. The bacterial suspensions of B-1662 showed an excellent biological control effect on the red pepper anthracnose and apple bitter rot using an in planta assay. The anthracnose disease rate (%) was controlled by over 90% with B-1662 cell suspensions at 105 to 107 CFU/mL. Compared to a control, the strain B-1662 played a more effective role in controlling the anthracnose disease in field conditions in both years 2022 and 2023. From the effective solvent fractions, the effect compound (dibutoxybutane) has been isolated exhibiting with antifungal effect. The genetic base underlying the biocontrol traits of B-1662 was characterized using the whole-genome sequence of B-1662, which was compared with closely related strains. Consequently, these results collectively suggest that S. sporoverrucosus B-1662 can aid in the management of red-pepper anthracnose.